2020
DOI: 10.1089/jir.2019.0241
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Elafin Ameliorates Chronic Hyperoxia-Induced Lung Injury by Inhibiting Nuclear Factor-Kappa B Signaling in Neonatal Mice

Abstract: The study aimed to investigate whether recombinant human elafin can prevent hyperoxia-induced pulmonary inflammation in newborn mice, and to explore the mechanism underlying the inhibitory effects of elafin on nuclear factor-kappa B (NF-kB) signaling pathway. Neonatal C57BL/6J mice were exposed to 85% O 2 for 1, 3, 7, 14, or 21 days. Then, elafin was administered daily for 20 days through intraperitoneal injection. After treatment, morphometric analysis, quantitative real-time polymerase chain reaction, termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In the present study, the expression levels of IL-6 and IL-8 were detected in the cells to explore the effect of PSO on the inflammatory response in IL-13-induced JME/CF15 cells. The IL-6 and IL-8 proteins in the cell supernatant were very small and difficult to collect, so the expression of IL-6 and IL-8 in the cells was measured (32). The expression levels of IL-6 and IL-8 in cells have been detected in numerous previous studies, in which the expression of IL-6 and IL-8 in the cell supernatant was not detected (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the expression levels of IL-6 and IL-8 were detected in the cells to explore the effect of PSO on the inflammatory response in IL-13-induced JME/CF15 cells. The IL-6 and IL-8 proteins in the cell supernatant were very small and difficult to collect, so the expression of IL-6 and IL-8 in the cells was measured (32). The expression levels of IL-6 and IL-8 in cells have been detected in numerous previous studies, in which the expression of IL-6 and IL-8 in the cell supernatant was not detected (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that two peptides may play an antiinflammatory role in the process of BPD. And previous studies have shown that the regulation of inflammation-related signal pathways such as p38 mitogen activated protein kinases (p38MAPK) signal pathways and nuclear factor-κB (NF-κB) signal pathway can reduce the level of pro-inflammatory cytokines, thus relieving the pulmonary inflammation of BPD [ 76 , 77 ]. Combined with previous studies, we consider that the two peptides secreted from hUC-MSCs may decrease the production of pro-inflammatory cytokines through inflammation-related signal pathways and further researches need to be conducted to validate the possible pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings indicated that two peptides may play an anti-in ammatory role in the process of BPD. And previous studies have shown that the regulation of in ammation-related signal pathways such as p38 mitogen activated protein kinases (p38MAPK) signal pathways and nuclear factor-κB (NF-κB) signal pathway can reduce the level of pro-in ammatory cytokines, thus relieving the pulmonary in ammation of BPD [78,79].…”
Section: Discussionmentioning
confidence: 99%